Enhanced magnetism and suppressed magnetoelastic coupling induced by electron doping in Ca1−xYxMnReO6. (15th June 2022) - Cavichini, A S; Orlando, M T D; Fantini, M C A; Tartaglia, R; Galdino, C W; Damay, F; Porcher, F; Granado, E
Abstract: The Ca2 MnReO6 double perovskite is a spin–orbit-assisted Mott insulator with exotic magnetic properties, including a largely non-collinear Mn 2+ spin arrangement and nearly orthogonal coupling between such spins and the much smaller Re 5 d magnetic moments. Here, the electron-doped compound Ca1− x Y x MnReO6 ( x = 0.1, 0.2 and 0.3) is reported and a detailed investigation is conducted for x = 0.3. Neutron and x-ray powder diffraction confirm that nearly full chemical order is maintained at the Mn and Re sites under the Y substitution at the Ca site. X-ray absorption measurements and an analysis of the Mn–O/Re–O bond distances show that the Mn oxidation state remains stable at +2 whereas Re is reduced upon doping. The electron doping increases the magnetic ordering temperature from T c = 121 to 150 K and also enhances significantly the ferromagnetic component of the Mn spins at the expense of the antiferromagnetic component at the base temperature ( T = 3 K). The lattice parameter anomalies at T c observed in the parent compound are suppressed by the electron doping. The possible reasons for the enhanced magnetism and the suppressed magnetoelastic coupling in Ca1.7 Y0.3 MnReO6 are discussed.